Penggunaan Media Pembelajaran Interaktif Berbasis Pendekatan Make A Match Pada Konsep Suhu Dan Kalor - Ali, Nursanti; Muksin, Marwiya (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2023)
Abstrak This study aims to determine the Use of Interactive Powerpoint Learning Media Based on the Make A Match Approach to the Concept of Temperature and Heat in Class XI Students of SMK Tarakani Galela. This type of research used is experimental research with a One Group present-posttes type design. This research was conducted on students of class XI SMK Tarakani Galela which amounted to 32 students spread over 2 classes and the sample in this study were students of class XI Industrial Chemistry I (experimental class). The results of the study obtained the average learning outcomes of students increased. The average posttest results using Interactive Powertpoint Learning Media Based on Make A Match Approach in the experimental class amounted to 78.75. The results of the hypothesis test analysis using the t test through the One Sample T test erantuan SPSS 21.0 obtained a tcount of 32.027> ttable value of 1.753 so that Ho is rejected and H1 is accepted which means an increase in learning outcomes by using interactive powertpoint learning media based on make a matrch.